Professor Emil RAJČAN - Editorial Board (Archives of Acoustics)
Prof. Emil Rajcan was born in Liptovská Osada on the 29th of March 1937, where he also completed primary education. He continued to study at the Grammar school in Ružomberok, which he finished in 1955. In 1959 he successfully graduated from the Pedagogical University in Bratislava, where he studied physics and mathematics. After finishing his study, he was assigned to Galanta as a teacher of physics and mathematics at a local grammar school. He married Eva Kollerová, and with his wife they had two sons, Rudolf and Emil.